Improved drought tolerant maize improved farmer yields and livelihoods benefiting 5.4 million households in eastern, western & southern Africa (DTMA, STMA) - CGIAR Research Program on Maize (2020)
The Drought Tolerant Maize for Africa (DTMA) and Stress Tolerant Maize for Africa (STMA) projects delivered improved drought- and stress-tolerant maize varieties to smallholder farmers. 200+ drought-tolerant (DT) maize hybrids and open-pollinated varieties (OPV) were released throughout DTMA?s lifetime, benefiting 5.4 million households. Under STMA (ended March 2020), MAIZE and partner scientists deployed over 100 stress-tolerant improved maize varieties, thanks to seed company partners providing 110,000 tons certified seed (2019). Eight million+ households planted them on 5 million hectares (2020).